2004
DOI: 10.1124/dmd.104.001438
|View full text |Cite
|
Sign up to set email alerts
|

Lansoprazole Enantiomer Activates Human Liver Microsomal Cyp2c9 Catalytic Activity in a Stereospecific and Substrate-Specific Manner

Abstract: ABSTRACT:We recently proposed a possible stereoselective activation by lansoprazole of CYP2C9-catalyzed tolbutamide hydroxylation, as well as stereoselective inhibition of several cytochrome P450 (P450) isoforms. This study evaluated the effects of lansoprazole enantiomers on CYP2C9 activity in vitro, using several probe substrates. For tolbutamide 4-methylhydroxylation and phenytoin 4-hydroxylation, Rlansoprazole was an activator (140 and 550% of control at 100 M R-lansoprazole, EC 50 values of 19.9 and 30.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
1
18
3
Order By: Relevance
“…Homotropic positive cooperativity has been observed for the human UGT2B7 nonselective substrate 4-methylumbelliferone (Miners et al, 2004) and estradiol 3-glucuronidation by the addition of UGT1A1 substrates (Williams et al, 2002). A similar effect has also previously been shown for cytochrome P450 enzymes in HLM, for example, in the activation of CYP2C9-catalyzed tolbutamide hydroxylation by lansoprazole (Liu et al, 2005) and for the stimulation of CYP3A4-mediated metabolism of warfarin by quinidine (Ngui et al, 2001). Although we were unable to obtain recombinant rat UGT1A1 and UGT1A7 to further investigate this effect and identify the UGT involved, these data are the first of their kind to suggest positive cooperativity in rat UGT.…”
Section: Mean (Sem) K M Values For the Control And Trmentioning
confidence: 48%
“…Homotropic positive cooperativity has been observed for the human UGT2B7 nonselective substrate 4-methylumbelliferone (Miners et al, 2004) and estradiol 3-glucuronidation by the addition of UGT1A1 substrates (Williams et al, 2002). A similar effect has also previously been shown for cytochrome P450 enzymes in HLM, for example, in the activation of CYP2C9-catalyzed tolbutamide hydroxylation by lansoprazole (Liu et al, 2005) and for the stimulation of CYP3A4-mediated metabolism of warfarin by quinidine (Ngui et al, 2001). Although we were unable to obtain recombinant rat UGT1A1 and UGT1A7 to further investigate this effect and identify the UGT involved, these data are the first of their kind to suggest positive cooperativity in rat UGT.…”
Section: Mean (Sem) K M Values For the Control And Trmentioning
confidence: 48%
“…On the other hand, several studies have demonstrated the enhancement of CYP2C9-mediated metabolism by some drugs, suggesting a two-site binding model as the underlying mechanism of the activation. [26][27][28] The exact reason for the different results between the studies by us and Zou et al is unclear, but the assay systems used may be the cause. We used the system of HLMs and probe substrates, whereas Zou et al employed the system of recombinant isoforms and synthetic substrates.…”
Section: Discussioncontrasting
confidence: 41%
“…The ligand-specific nature of the metabolic profiles across the range of mutants studied suggests that phenytoin, (S)-warfarin, and the NSAIDs each interact in a unique fashion with CYP2C9 active-site amino acids during catalytic turnover. This conclusion complements that made by Liu et al (2005), who found that the addition of (R)-lansoprazole had differential effects on the metabolism of these same three ligands. Phenytoin is a very useful drug with which to probe substrate positioning during catalysis by CYP2C9 because both the regio-and stereochemistry of product formation can be monitored (Scheme 1).…”
Section: Discussioncontrasting
confidence: 33%